Integrasi Alquran dan Materi Pembelajaran Kurikulum Sains pada Tingkat Sekolah di Indonesia: Langkah Menuju Kurikulum Sains Berbasis Alquran - Abdurrohim Harahap (Universitas Islam Negeri Sumatera Utara, 2018)
This paper attempts to outline the importance of integrating Alquran with learning materials at the school level. This study is specifically intended to examine the verses kawniyyāt and related them to the material in the science curriculum in secondary schools, and then make Alquran the main reference. Using content analysis methodology, this study seeks to integrate science verses and science curriculum materials in schools. In addition to this study seeks to find similarities and comparisons between verses kawniyyāt in Alqur’an and science curriculum, which then collect them into an integration of material, so as to produce a way to integrate Alquran and science curriculum learning material at the secondary school. This concludes that the development of the model of integration of Alquran and the science curriculum can be done in three stages; first, analyzing all verses kawniyyat in the Qur'an and which are relevant to the discussion. Secondly, analyzing the material of the discussion of the science curriculum relating toverses kawniyyat, and the third, integrating the verses kawniyyat against the discussion material in the science curriculum.